The evaluation study of Mashashane breeder farms and hatchery project. - Kganyago, Tshoshane Gladys (My University, 2009)
This report describes the research carried out at both the Mashashane Breeder Farms and Hatchery Project established at Newlands village (Mashashane), of Polokwane Municipality of the Capricorn region of Limpopo Province in South Africa. This research is about the sustainability of projects in Limpopo Province of South Africa. For this purpose, the Mashashane Breeder Farms and Hatchery Project is the case of this study. The study aimed at evaluating the sustainability of the Mashashane Breeder Farms and Hatchery Project, so as to make authorities aware of the difficulties experienced in sustaining projects, and to highlight those factors that make projects succeed. The following research questions were formulated for this study: • What are the critical factors that determine sustainability of projects? • What can be the role of adult education in this project? The intention of this study was to investigate why most projects collapse; and what kept the Mashashane Breeder Farms and Hatchery Project to exist for such a long time. In Chapter 2 of this study, I formulated assumptions about the sustainability of projects. I suggested certain factors to be considered for the purpose of sustaining a project. My assumptions were needs analysis; organising people; communication; competition; management; deliverables; lack of skills; ability to plan; project ownership and participation; the role of the government; and time table (schedule). In Chapter 3, the methodology is outlined. This study followed the qualitative approach. Instruments used for the collection of data are also explained. I discussed the main learning area, outlined the difficulties in carrying out the research activities and concluded the chapter by the model of data matrix. In Chapter 4 of this study, findings from Mashashane Breeder Farms and Hatchery Project are outlined, based on documents, interviews and observations of activities of the project. I formulated variables informed by Chapter 2 of this study. I report on the setting of the Mashashane Breeder Farms and Hatchery Project. In Chapter 5, I have outlined conclusions based on the study. The suggested points about a good project are tabled. Inclusive of the challenges faced by the Mashashane Breeder Farms and Hatchery project are, namely: mortality; infertility; no income period; and education and training of employees. In Chapter 6, I have given recommendations for this study. Some of the recommendations specifically for this project are, namely: more projects should be established to address unemployment and poverty; feedback should be given to employees; communication should be reciprocal, prior work experience be recognised; adult education should be introduced for employees to upgrade their skills and develop some; workshops should be arranged to improve lives of employees; and increasing production and competition is to be encouraged at all levels (internally and externally).
Thesis (M.Ed)--University of Limpopo,2009.
Keywords: Breeder farms; Hatchery project; Mashashane Village, Limpopo; 658.4040968; Project management